Fast fourier transform in ofdm: algorithmic approaches and their role in information technologies - Бойко, Ю.; Пятін, І.; Дружинін, Володимир Анатолійович; Єрьоменко, О. (Київський національний університет імені Тараса Шевченка, 2025)
Background. Orthogonal Frequency Division Multiplexing (OFDM) is a key technology in modern information systems and is widely used in mobile networks such as 4G and 5G, the IEEE 802.11 standard (Wi-Fi), and digital television (DVB-T). The increase in the communication channel bandwidth requires an optimal selection of signal transformation parameters for efficient use of the hardware resources of Field-Programmable Gate Arrays (FPGA) in the implementation of OFDM.Methods. The following methods were used: modeling of an OFDM-based communication system in the Simulink environment, which allowed for the study of signal processing transformations, as well as the analysis of the bit error rate (BER) for different modulation parameters. The implementation of FFT algorithms was carried out using HDL coding to compare the efficiency of the Fast Fourier Transform (FFT) algorithms Streaming Radix-2² and Burst Radix-2.Results. Simulation results showed that using signal resampling at the transmitter improves the channel energy efficiency, reducing the required power level by 12 dB. The relationship between the bit error rate and the signal-to-noise ratio (SNR) demonstrates that increasing the FFT length from 512 to 2048 points requires a 6 dB increase in the SNR. The analysis of the cyclic prefix (CP) impact showed that the optimal CP length is 1/16 of the OFDM symbol, which reduces transmission speed losses. The effect of modulation on the bit error rate (BER) indicates the need for increased power when transitioning to higher-order Quadrature Amplitude Modulation (QAM).Conclusions. It was concluded that the parameters of FFT and signal resampling are critical for the efficiency of the OFDM system. The results obtained can be used to optimize the implementation of OFDM on FPGA.

Вступ. Технологія мультиплексування з ортогональним частотним поділом каналів – OFDM (Orthogonal frequency-division multiplexing) є ключовою технологією сучасних інформаційних систем і використовується в мобільних мережах 4G, 5G, стандарті IEEE 802.11 (Wi-Fi) і цифровому телебаченні (DVB-T). Збільшення пропускної здатності каналів зв'язку вимагає оптимального вибору параметрів перетворень сигналів для ефективного використання апаратних ресурсів програмованої вентильної матриці FPGA (Field-programmable gate array) для реалізації OFDM.Методи. Використано такі методи: математичне моделювання системи зв'язку з OFDM у середовищі Simulink, що дозволило дослідити функціональні перетворення сигналу, а також аналіз коефіцієнта бітових помилок для різних параметрів модуляції. Реалізацію алгоритмів FFT виконано з використанням HDL-кодування для порівняння ефективності алгоритмів швидкого перетворення Фур'є (FFT) Streaming Radix-2² і Burst Radix-2.Результати. Результати моделювання показали, що використання передискретизації сигналу на передавачі покращує енергетику каналу, знижуючи необхідний рівень потужності на 12 дБ. Залежність коефіцієнта бітових помилок від відношення сигнал-шум демонструє, що збільшення довжини FFT з 512 до 2048 точок потребує підвищення відношення сигнал / шум SNR на 6 дБ. Аналіз впливу циклічного префікса (СP) показав, що оптимальна довжина CP становить 1/16 символу OFDM, що зменшує втрати швидкості передачі. Вплив модуляції на коефіцієнт бітових помилок (BER) свідчить про необхідність збільшення потужності під час переходу до вищих порядків квадратурної амплітудної модуляції (QAM).Висновки. Зроблено висновок, що параметри FFT і передискретизації є критичними для ефективності системи OFDM. Отримані результати можуть бути використані для оптимізації реалізації OFDM на FPGA.
Швидке перетворення Фур'є в OFDM: алгоритмічні підходи та їхня роль в інформаційних технологіях
Keywords: Orthogonal Frequency Division Multiplexing (OFDM); Fast Fourier Transform (FFT); Information Systems; Bit Error Rate (BER); Field-Programmable Gate Array (FPGA); ортогональне частотне мультиплексування (OFDM); швидке перетворення Фур'є (FFT); інформаційні системи; коефіцієнт бітових помилок; програмована вентильна матриця (FPGA)